Gap characteristics and regeneration in Bwindi Impenetrable National Park, Uganda - Babaasa, Dennis; Eilu, Gerald; Kasangaki, Aventino; Bitariho, Robert; McNeilage, Alastair (African Journal of Ecology, 2004)
Before Bwindi Impenetrable forest, Uganda, became a national park in 1991, there was a high level of human activity in much of the forest, especially cutting of large trees for timber by pitsawyers. This created extensive gaps in this tropical Afromontane rain forest. We quantified and compared tree regeneration in three sites that were logged at different intensities. Gap sizes in Bwindi, even under fairly natural conditions are very large (mean ¼ 4460.1 m2). Logging further enlarged the gap sizes and had a negative impact on tree regeneration. The study shows the strong role of logging disturbance in promoting an alternative successional pathway, where the large gaps created by logging are in a low-canopy state dominated by a dense tangle of herbs, shrubs, and herbaceous or semiwoody climbers. We recommend periodic monitoring of gap size and tree regeneration in the gaps to ascertain the trend of recovery from past logging disturbance.
Keywords: Bwindi impenetrable; gap dynamics; gap size; succession; Uganda